Quantification of Superficial Venous Reflux by Duplex Ultrasound - Role of Peak Reflux Velocity and Reflux Time in the Assessment of Varicose Vein - Singh, Amit Kumar; Karmacharya, Robin Man; Vaidya, Satish; Thapa, Pratima (Journal of Nepal Health Research Council, 2020)
Background: The study compared the peak reflux velocity and reflux time in cases of varicose veins and non-varicose veins with a focus on quantifying the reflux parameters.Methods: This is a hospital based observational comparative study. The limbs with CEAP Clinical classification of C2 or more were taken as diseased limbs and contra-lateral limbs with no symptoms or disease were taken as control limbs.Results: Altogether 792 limbs (452 diseased limbs and 340 control limbs) were evaluated with color duplex. Mean Great Saphenous Vein diameter was 5.68 ± 2.07 mm and 4.00 ± 1.34mmin diseased limbs and control limbs respectively (p=0.0001). Mean sapheno-femoral junction diameter was 8.23 ± 2.64 mm and 6.16 ± 1.93 mm in diseased limbs and control limbs respectively (p=0.0001). Mean peak reflux velocity in diseased limbs was significantly higher than control limbs (77.38 cm/sec vs 7.95 cm/sec; p=0.0001).  Similarly mean reflux time was significantly longer in diseased limbs than non-diseased limb (406.58ms and 67.28 ms respectively; p=0.0001). An optimal cut-off point of 27.4 cm/s for peak reflux velocity and 250 ms for the reflux time at Sapheno-Femoral junction had a discriminatory power between the two groups.Conclusion: The quantification of peak reflux velocity seems to be more consistent than reflux time in determining the superficial venous reflux. An optimal peak reflux velocity cut off point of 27.4 cm/sec has the discriminatory power between diseased and non-diseased limb.Keywords: Peak reflux velocity; reflux time; superficial venous insufficiency; ultrasound color duplex; varicose veins